2018
DOI: 10.1002/jcb.26471
|View full text |Cite
|
Sign up to set email alerts
|

Functional SNP in microRNA‐491‐5p binding site of MMP9 3′‐UTR affects cancer susceptibility

Abstract: MicroRNAs (miRNA) are small RNA molecules that negatively regulate gene expression through base pairing interactions between 3'-UTR of the target mRNAs and seed sequence of miRNA. Any changes in the recognition site could destroy binding sites or modify binding affinity, resulting in evasion from miRNA regulation. A putative binding site for miR-491-5p resides in 3'-UTR of MMP9, and a genetic variant (rs1056628 A → C) is present in this region. The role of MMP9 over expression well marked in various cancers. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…MMP-9, a member of the MMP family, has been previously demonstrated to mediate trophoblast invasion and migration (32)(33)(34); for example, Rasstrigina et al (35) reported that the decreased expression levels of MMP-9 in the placenta contributed to the reduced invasiveness of trophoblasts. Notably, a previous study also observed that miR-491-5p suppressed the invasive ability of gastric, breast and lung cancer cells through targeting MMP-9 (36). Nonetheless, whether MMP-9 was implicated in the inhibitory effects of miR-491-5p on trophoblastic invasion remained relatively unknown.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-9, a member of the MMP family, has been previously demonstrated to mediate trophoblast invasion and migration (32)(33)(34); for example, Rasstrigina et al (35) reported that the decreased expression levels of MMP-9 in the placenta contributed to the reduced invasiveness of trophoblasts. Notably, a previous study also observed that miR-491-5p suppressed the invasive ability of gastric, breast and lung cancer cells through targeting MMP-9 (36). Nonetheless, whether MMP-9 was implicated in the inhibitory effects of miR-491-5p on trophoblastic invasion remained relatively unknown.…”
Section: Discussionmentioning
confidence: 99%
“…And also found the miRNAs expression changes in gastric cancer [11][12][13] . Recently discovered miRNA miR-491, is downregulated in several types of cancer, including breast cancer, oral squamous cell carcinoma, hepatocellular carcinoma, pancreatic, glioblastoma, ovarian cancer and hepatocellular carcinoma [13][14][15] . miR-491-5p has been shown to be a mature form of miR-491 that induce apoptosis and inhibit the proliferation of pancreatic, ovarian, breast cancer and colorectal cells, as well as the migration and invasion of glioma and breast, oral squamous cell.…”
Section: Discussionmentioning
confidence: 99%
“…SNPs in miRNA binding sites have been associated with cancer risk and outcomes. Alterations in these sites could modify the binding sites or change the binding affinity, leading to escape from miRNA regulation [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%